Timing the Application of Beneficial Nematodes to Mole Cricket Activity on Pasture to Optimize Control - Martin B. Adjei; G. C. Smart, Jr.; J. Howard Frank; Norman C. Leppla (EDIS)
Revised! ENY-663, a 3-page illustrated fact sheet by M.B. Adjei, G.C. Smart, Jr., J.H. Frank and N.C. Leppla, provides guidance for optimizing a match between infective juvenile Ss nematodes and mole cricket hosts, and also describes the process for applying this biological control agent to pastures and turfgrasses. This version includes updated recommendations. Published by the UF Department of Entomology and Nematology, August 2006.